Environmental Monitoring and Assessment An International Journal Devoted to Progress in the Use of Monitoring Data in Assessing Environmental Risks to Man and the Environment - Wiersma, G. Bruce; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Environmental Monitoring and Assessment emphasizes technical developments and data arising from environmental monitoring and assessment, the use of scientific principles in the design of monitoring systems at the local, regional and global scales, and the use of monitoring data in assessing the consequences of natural resource management actions and pollution risks to man and the environment. The journal covers a wide range of pollutants and examines monitoring systems designed to estimate exposure both at the individual and population levels. The journal also focuses on the development of monitoring systems related to the management of various renewable natural resources in, for instance, agriculture, fisheries and forests. The scope of the journal extends to the use of monitoring in pollution assessment, and particular emphasis is given to the synthesis of monitoring data with toxicological, epidemiological and health data, as well as with pre-market screening results. The journal also includes research and monitoring systems that help assess anthropogenic impacts on natural resources and the environment from numerous activities, such as harvesting, development, and land use changes. Geographic information system analyses and remote sensing studies relating such activities to land cover changes that affect, e.g. biodiversity and global climate change are also within the purview of the journal. Examples of specific areas of interest are: The design and development of single medium and multimedia monitoring systems, sampling techniques, optimization of monitoring networks, data handling, quality and assurance procedures, operational costs. The scientific basis for monitoring: scaling methods, the use of biological indicators, dynamic and commitment models, pollution indices, etc. Exposure assessment: the development of monitoring systems which allow direct or indirect estimates of pollutant exposure to critical receptors. Methods and procedures of pollution risk assessment, relating to sources, pathways of exposure, trends in time and space, anticipatory systems, evaluation of environmental quality and of management practice. Monitoring systems designed to detect changes in land use patterns.
Keywords: Ecology; Environmental monitoring; Environmental management; Ecotoxicology; Air pollution; Monitoring/Environmental Analysis; Environmental Management; Ecotoxicology; Atmospheric Protection/Air Quality Control/Air Pollution; Ecology